Reef fish community structure in the islands of Paraja Bay, Pandeglang District, Banten, Indonesia - MUJIYANTO MUJIYANTO; YAYUK SUGIANTI; YUSUF ARIEF AFANDY; RISNAWATI RAHAYU; R. ARIEF BUDIKUSUMA; ADRIANI SRI NASTITI; AMRAN RONNY SYAM; SRI ENDAH PURNANINGTYAS (Society for Indonesian Biodiversity, 2021)
Abstract. Mujiyanto, Sugianti Y, Afandy YA, Rahayu R, Bidikusuma RA, Nasriri AS, Syam AR, Purnaningtyas SE. 2021. Reef fish community structure in the islands of Paraja Bay, Pandeglang District, Banten, Indonesia. Biodiversitas 22: 4402-4413. Paraja Bay waters have five small islands that coexist with Ujung Kulon National Marine Park and act as a buffer zone for the diversity of fishery resources. This study aimed to assess the reef fishes community structure at small islands in Paraja Bay. Observations were made in 20 locations during August and September 2019 in the five small islands. Reef fishes community structure showed 106 species as included major group (54 species), indicator group (24 species) and target group (28 species), among five small islands, i.e. Badul, Mangir, Oar, Sumur and Umang Islands. The highest reef fishes abundance was founded in Umang Island waters. Several target fish species recorded during the study were mature fish (such as those targeted by fishermen). Only a small proportion were juveniles. Reef fish community structure was categorized as stress community to stable community with its indication was low diversity value, high evenness index, and low dominance. The low diversity index value illustrates that the level of uniformity of reef fish species in Paraja Bay waters is high. This condition is evidenced by each coral fish group's evenness index included in the main species group around 0.93 to 0.98. The target species is 0.88 to 0.99.